Brand community relationships transitioning into brand relationships: Mediating and moderating mechanisms. (November 2018) - Kumar, Jitender; Nayak, Jogendra Kumar
Abstract: We aim at identifying and examining the different patterns of mechanisms through which the community-based relationships result in brand-based relationships. Hence, we address the gaps of identifying and engaging in a community for the generation of loyal customers of a specific brand, which is mediated by the customers' brand engagement. We have collected data from 240 brand community members in India and conducted the empirical analysis through a partial least square-structural equation modeling technique. The results have indicated that customers brand engagement (CBE) fully mediates the relationship between brand community engagement and loyalty intentions, and partially mediates the relationship between customer brand identification and loyalty intentions. A sense of community-brand congruity has a moderating effect in the transition of community-based relationships into brand-based relationships. This study provides new evidence to the academicians and practitioners for guiding their understanding of brand management through brand communities.